Electric discharge machining using rapid manufactured complex shape copper electrode with cryogenic cooling channel. (January 2021) - Singh, Jagtar; Singh, Gurminder; Pandey, Pulak M
In this study, a rapid manufacturing process based on the combination of polymer three-dimensional printing and pressureless loose sintering was explored for the fabrication of complex shape electric discharge machining pure copper electrodes with the cryogenic cooling channel. The fabricated electrodes were used to perform electric discharge machining on D2 steel workpiece. The comparative study was performed on material removal and electrode wear rates between the solid copper electrode, rapid manufactured electrode without cryogenic cooling and with cryogenic cooling. Also, the surface characteristics of the worn electrode and the machined workpiece were studied with and without cryogenic cooling. The significant effect of the cryogenic cooling on the electrode wear rate and the surface roughness was observed. Better surface finish, small cracks and less debris were notified on the workpiece surface machined with rapid manufactured electrode with cryogenic cooling due to rapid dissipation of the heat from the surface of the electrode after machining. Similarly, few cracks and low carbon deposition was observed on the rapid manufactured electrode with cryogenic cooling surface after machining as compared to rapid manufactured electrode without cryogenic cooling. The sharp corner edges of the complex shape tool in rapid manufactured electrode with cryogenic cooling were retained after machining due to low melting and vaporization of the electrode material. The dimensional deviation of the machined surface with respect to computer-aided design model was compared. The rapid manufactured electrode with cryogenic cooling was found to machine the more accurate complex shape features in terms of dimensions on the workpiece as compared to rapid manufactured electrode without cryogenic cooling.